MITIGASI SHARIA NON-COMPLIANCE RISK PENGEMBANGAN PRODUK KEUANGAN SYARIAH DI BANK PEMBIAYAAN RAKYAT SYARIAH (Studi Kasus : PT. BPRS Mandiri Mitra Sukses) - Ahmad Hafid Afandi; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2018)
This research aims to analyze risk mitigation of Sharia Non-Compliance on thefinancial product development in the sharia financing bank. Risk mitigation of sharia noncompliance was including analization of product development proposal, analization of product study by director, analization of product study by commissioner, analization of study by sharia supervisor council (DPS). The method thatbused in this study was qualitative descriptive approach using study case on PT. Sharia Financing Bank (BPRS) Mandiri Mitra Sukses. The validation technic done using triangulation technic of source and technic. The analysis technic in this study was analysis technic of Miles and Huberman. The result of this study according to the steps of product development risk mitigation of sharia non-compliance that presented the process of publishing product conducted by company management. Based on analysis that has been done by researcher, PT. BPRS Mandiri Mitra Sukses already capable to perform risk mitigation.REFERENCESAntonio, Muhammad Syafi’i.2001. Bank Syariah: Dari Teori ke Praktek.Jakarta: Gema Insani PressBank Indonesia.2011. Peraturan Bank Indonesia No. 13/23/PBI/2011 tentang Penerapan Manajemen Risiko Bagi Bank Umum Syariah Dan Unit Usaha Syariah. JakartaHartono, Sri Redjeki. 1995. Hukum Asuransi dan Perusahaan Asuransi.Jakarta: Sinar Grafika, hlm.62IFSB, Islamic Financial Service Board.2005. Guiding Principles of Risk Management for Institution (Other Than Insurance Institution), offering only Islamic Financial Service, hlm. 26Ilhami, Haniah.2009. Pertanggungjawaban Dewan Pengurus Syariah Sebagai Otoritas Pengawas Kepatauhan Syariah Bagi Bank Syariah, Jurnal Mimbar Hukum, Volume 21 Nomor 3, Oktober 2009, hlm..477 Kementrian Agama RI. 2014. Mushaf At-Tammam Al-Qur’an dan Terjemahnya. Solo : PT.Tiga Serangkai Pustaka MandiriLahsasna, Ahcene.2014.Shari’ah Non-Compliance Risk Management and Legal Documentation in Islamic Finance.Singapore: Wiley Finance Series. Lewis, Mervyn K dan Lativa M.Algaoud. 2007. Perbankan Syariah: Prinsip, Praktik dan Prospek. Jakarta: PT. Serambi Ilmu Semesta. halm 215Otoritas Jasa Keuangan.2015. Salinan Surat Edaran Otoritas Jasa Keuangan  Nomor 37/Seojk.03/2015 Tentang Produk dan Aktivitas Bank Pembiayaan Rakyat Syariah. JakartaYin. Robert K. 2003. Studi Kasus: Desain dan Metode, Terjemahan. Jakarta: PT Raja Grafindo PersadaRivai dan Ismail.2013.Islamic Risk Management For Islamic Bank: Jakartahttp://www.bi.go.id/peraturan/arsipperatran/perbankan2003/pbi-5-8-2003.pdf.                      Diakses pada tanggal 09/02/2017http://finansial.bisnis.com/read/20151103/90/488554/peyelewengan-pemberian-kredit-dominasi-kasus-perbankan.                Dimuat pada 03 november 2015 jam 19:18 wib di Malang, diakses pada tanggal 20 april 2017 jam 06.29 WIB.